Colorectal cancers metastases clinicopathology, and PET/CT - Cinar, Alev; Cayir, Derya (Journal of the Pakistan Medical Association, 2026)
Objective: To investigate the difference in primary tumour locations according to the organs to which colorectal cancers metastasised. Method: The retrospective study was conducted at the Health Sciences University, Gulhane Training and Research Hospital, Ankara, Turkiye, and comprised data from January 2011 to January 2021 of metastatic colorectal cancer patients. The data was divided into three groups based on their primary tumour locations as per the positron emission tomography and computed tomography images. The ascending colon and transverse colon were categorised as right-sided and placed in group 1, the descending colon and sigmoid colon were categorised as left-sided and placed in group 2, while rectal cancers were placed in group 3. The groups were compared in terms of the organs to which their cancer metastasised. Data was analysed using SPSS 15. Results: Of the 83 patients, 52(62.6%) were males and 31(37.4%) were females. The overall mean age was 63.58±10.2 years (range: 34-87 years). There were 44(53%) patients in group 1, 22(26.5%) in group 2, and 17(20.5%) in group 3 (p=0.053). Liver alone encountered metastases in 48(57.8%) cases. The frequency of only lung metastasis, and only liver metastasis in group 1 was higher than the other groups (p=0.001). There was no significant difference among the groups in terms of synchronous metastatic spread of cancer to both the liver and the lungs (p=0.031). Conclusion: The right-sided colon tumours had a higher potential to metastasise compared to the other colon cases. Key Words: Colorectal cancer, Metastases physiology, PET, CT.